Drug-Drug Interaction of Aldehyde Oxidase Inhibitor and Xanthine Oxidase Inhibitor with Favipiravir - Özek, Dilan Aşkın; Alkaç, Zeliha Keskin; Yüce, Hande; Türkmen, Neşe Başak; Aslan, Sümeyye; Ünüvar, Songül (My University, 2022)
Aim: Favipiravir is an effective antiviral used in the treatment of COVID-19. It is metabolized by aldehyde oxidase (AO) and xanthine oxidase (XO). This study investigated drug-drug interactions between favipiravir with both AO substrate and XO enzyme inhibitor, allopurinol, and an XO inhibitor, verapamil. Material and Methods: 25 Sprague-Dawley female rats, 250-300 g, were divided into five equal groups. Blood samples were taken from the jugular vein at the end of 0, 15, 30, and 45 minutes, and at the end of the 1st, 2nd, 4th, 6th, and 8th hours after the drugs were administered. The drug-blood concentration was determined in the HPLC-UV device using plasma. The ELISA method measured AO and XO enzyme activities in rat liver tissue. Results: Allopurinol prolonged the time taken for favipiravir to reach Cmax (Tmax), decreased maximum serum concentration (Cmax), elimination half-life (T1/2), area under the curve (AUC), and mean residence time (MRT). Allopurinol significantly reduced clearance per unit time (Cl/f) when co-administered with favipiravir. Verapamil accelerated the elimination of favipiravir, significantly reducing T1/2, MRT, and AUC. On the other hand, Favipiravir decreased the absorption of verapamil and slowed its elimination. Cmax, AUC, and Cl values of verapamil decreased. In addition, T1/2, MRT, and volume of distribution (Vd) increased. Conclusion: In conclusion, the concomitant use of favipiravir with other drugs that affect AO and/or XO enzyme activities may cause changes in the pharmacokinetic profiles of drugs and the levels of enzymes that metabolize drugs.
Keywords: Pharmacokinetics; allopurinol; Favipiravir; verapamil; aldehyde oxidase